Green official development Aid and carbon emissions: do institutions matter?. (10th February 2021) - Li, Dmitriy D.; Rishi, Meenakshi; Bae, Jeong Hwan
Abstract: This paper examines whether green Official Development Aid (ODA) has a significant role in mitigating carbon emissions in recipient countries, and if institutional quality matters for the effectiveness of green ODA. For 86 green ODA recipient countries over the period 2003–2014, we explore the nexus between green ODA, institutions and carbon emissions. By using a two-step system generalized method of moment (GMM), we find that green ODA overall has no direct association with the mitigation of carbon emissions. However, when institutional quality indices are included, we found a significant effect of institutional quality on the effectiveness of green ODA. In general, green ODA is associated with higher carbon emissions in countries with poor institutions. In particular, green ODA is effective in mitigating carbon emissions when channeled to countries that enjoy higher economic freedom as well as more freedom from corruption. Results are mixed for the rule of law.